DAYA SAING PENDIDIKAN: REVIEW ATAS PONDASI DAN IMPLEMENTASI KEBIJAKAN - *, Muslishudin (IAIN Pekalongan, 2010)
The competitiveness of the global community of education deals with the problems of humanity. For that reason the development of curriculum should consider the major issues that developed in the global world. The curriculum that may be developed is an “eclectic” between humanistic approach, reconstruction of social and academic. Meanwhile, the learning approach can be implemented with “experiental learning”. From the government side should be put through categorization of the school on formal education, therefore the competitiveness of national education will experience acceleration.